Exploring the Connection: Women's Product Preferences and Retail Environments in Haryana - Jyoti, Pooja (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2022)
This research delves into the intricate dynamics between product preferences and shopping environments among women in Haryana, aiming to uncover nuanced insights into consumer behavior. Through a comprehensive study encompassing both rural and urban settings, the research employs surveys and interviews to gather data. Initial findings suggest a multifaceted relationship, with product preferences influenced by the distinct shopping environments prevalent in Haryana. The research contributes valuable insights into tailoring marketing strategies that resonate with the diverse preferences of women consumers in Haryana, ultimately enhancing the effectiveness of product offerings in both rural and urban contexts. This exploration is pivotal for fostering informed decision-making in the realm of retail and consumer engagement.